Genome Divergence and Dynamics in the Thin-Tailed Desert Sheep From Sudan - Abied, Adam; Ahbara, Abulgasim M.; Berihulay, Haile; Xu, Lingyang; Islam, Rabiul; El-Hag, Faisal M.; Rekik, Mourad; Haile, Aynalem; Han, Jian-Lin; Ma, Yuehui; Zhao, Qianjun; Mwacharo, Joram M. (Frontiers in Genetics, 2021)
With climate change bound to affect food and feed production, emphasis will shift to resilient and adapted indigenous livestock to sustain animal production. However, indigenous livestock comprise several varieties, strains and ecotypes whose genomes are poorly characterized. Here, we investigated genomic variation in an African thin-tailed Desert Sheep sampled in Sudan, using 600K genotype data generated from 92 individuals representing five ecotypes. We included data from 18 fat-tailed and 45 thin-tailed sheep from China, to investigate shared ancestry and perform comparative genomic analysis. We observed a clear genomic differentiation between the African thin-tailed Desert Sheep and the Chinese thin-tailed and fat-tailed sheep, suggesting a broad genetic structure between the fat-tailed and thin-tailed sheep in general, and that at least two autosomal gene pools comprise the genome profile of the thin-tailed sheep. Further analysis detected two distinct genetic clusters in both the African thin-tailed Desert Sheep and the Chinese thin-tailed sheep, suggesting a fine-scale and complex genome architecture in thin-tailed sheep. Selection signature analysis suggested differences in adaptation, production, reproduction and morphology likely underly the fine-scale genetic structure in the African thin-tailed Desert Sheep. This may need to be considered in designing breeding programs and genome-wide association studies.